2006
DOI: 10.1167/iovs.06-0378
|View full text |Cite
|
Sign up to set email alerts
|

Control of Filtering Bleb Structure through Tissue Bioengineering: An Animal Model

Abstract: Implantation of a biodegradable, porous collagen matrix in the subconjunctival space offers the potential for a new means of avoiding early scar formation and maintaining long-term IOP control by creating a loosely structured filtering bleb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 20 publications
0
86
0
4
Order By: Relevance
“…It led to a randomised collagen deposition and microcyst formation after penetrating anti-glaucomatous surgery in contrast to the negative control and decreased early postoperative scarring. 8,9 Moreover, the ologen implant will also be adjuvant in repairing postoperative bleb leaks. 9 In human subjects, the ologen implant was tested for augmentation in deep sclerectomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It led to a randomised collagen deposition and microcyst formation after penetrating anti-glaucomatous surgery in contrast to the negative control and decreased early postoperative scarring. 8,9 Moreover, the ologen implant will also be adjuvant in repairing postoperative bleb leaks. 9 In human subjects, the ologen implant was tested for augmentation in deep sclerectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the biodegradable implant decreased early postoperative scarring. 8 A prospective pilot study revealed no significant difference in the postoperative IOP after trabeculectomy in the control group and trabeculectomy with ologen in the study group. 10 In a prospective, randomised study with two interventional groups, we investigated the ologen implant as an alternative for modulation of wound healing in anti-glaucomatous surgery.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The Ologen collagen matrix is a biodegradable porcine-derived collagen-glycosaminoglycan matrix that has been shown to decrease early post-operative scarring in animal models [6,7]. When Ologen is placed directly over the scleral flap, fibroblasts migrate into the pores.…”
Section: Introductionmentioning
confidence: 99%